Net Irrigation Requirements for Florida Turfgrass Lawns: Part 1 - Report of Gathered Weather Data and Quality Check - Consuelo C. Romero; Michael D. Dukes (EDIS, 2011)
Urban water users need specific recommendations to irrigate efficiently and for planning and regulatory programs. The first step in the process of estimating net irrigation requirements is to check the quality of 30 years of weather data at ten different locations in Florida and one in Alabama. This 9-page fact sheet was written by Consuelo C. Romero and Michael D. Dukes and published by the UF Department of Agricultural and Biological Engineering, August 2011. (AP photo by Milt Putnam, University of Florida/IFAS)